From hand to handle the first industrial revolution - Barham, Lawrence (Oxford Oxford University Press, 2013)
This volume brings together evidence for the cognitive, social, and technological foundations necessary for the development of hafting, or the addition of handles and shafts to previously hand-held tools, which made the tools not only more efficient, but improved their makers' chances of survival.
Includes bibliographical references and index.
Keywords: Electronic books; Paleolithic period; Tools, Prehistoric